ANALISIS BIAYA TRANSPORTASI DISTRIBUSI PUPUK MENGGUNAKAN SOFTWARE LINGO: PERBANDINGAN BIAYA TRANSPORTASI DISTRIBUSI PUPUK MENGGUNAKAN SOFTWARE LINGO - Fitria Noor Aida; Windi Rahmanda (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
The distribution of fertilizers in Central Sulawesi Province has not been efficient due to the large transportation costs in March 2016, the distribution of fertilizers could not go directly to retailers because the distance between regencies was far enough so that fertilizer was sent to distributors before to retailers to minimize costs to be incurred. company. Transhipment problems are in the form of indirect distribution problems because the products sent must go through several stages before reaching the consumer. This study will compare the Vogel Approximation method in previous studies with the completion of linear programming with Lingo software tools. Transportation costs using the Vogel Approximation method in previous studies compared with transportation costs using the Lingo software tool have the same cost of IDR 508,289,000, but there are several different fertilizer distributions. Lingo software simplifies data processing so that the results obtained are more accurate than the Vogel Approximation method. Companies can use lingo software to minimize costs by working effectively and efficiently.